Methodology for Assessing the Influence of Cultural Infrastructure on Regional Development in Poland and Ukraine - Alona Revko; Mykola Butko; Olha Popelo (Comparative Economic Research. Central and Eastern Europe, 2020)
The aim ofthe article isto characterize the level ofthe region's diversification according to the cultural component of social infrastructure based on grouped statistical indicators. This paper uses Perkal's synthetic ratio method to characterize the level of cultural infrastructure development in Ukrainian and Polish regions. The analysis, conducted between 2010 and 2017, concerned cultural organizations such as libraries, theaters, concert organizations, museums, cinemas, art and sports schools, and was based on regional data of Polish and Ukrainian public statistics. It was found that the primary barriers to access to cultural infrastructure are in adequate funding, disa-bility, geographic remoteness, disparities in education, and material living conditions. The determinants of modernizing cultural infrastructure in the region are defined.
Keywords: R1; O15; Z1; 330; social infrastructure; cultural infrastructure; human development; regional development